Mamluk Study in Europe and USA - Б.Н., Жубатова; Қ. Рaхимжaновa (Journal of Oriental Studies, 2019)
The aim of the article is to provide an overview of the study of the Mamluk era in the Middle East (about 1100-1500) in Europe and the USA, where Mamluk studies took place as an independent field of science. In the development of Mamluk studies in the West an important role play such scientific organizations as the Middle East Documentation Center at the University of Chicago (MEDOC), the Center of History and Society at the Mamluk Era (1250–1517) named after Anna Marie Schimmel Kolleg at the University of Bonn (Germany) and School of Mamluk Studies, which was organized by the efforts of scientists from Chicago (USA), Liege (Belgium) and Venice (Italy). The organizations mentioned carry out projects such as organizing annual conferences, conducting seminars, publishing the scientific journal Mamluk Studies Review, online bibliography of Mamluk Studies, online encyclopedia of Mamluk Studies, interactive online maps of the Mamluk Sultanate, web resource Mamluk Mint Series, development and programming of a database of Arabic translation into English. The information provided will be useful for researchers, scientists and students in the search of materials on the history and culture of Mamluks, as well as for the leaders of the centers as a European model for the development of such activities in the future. Key words: Mamluk Studies, Mamluk Studies centers, School of Mamluk Studies, conference, scientific journal, online maps, online encyclopedia.